2021
DOI: 10.1097/wco.0000000000000995
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral white blood cell responses as emerging biomarkers for patient stratification and prognosis in acute spinal cord injury

Abstract: Purpose of review To date, prognostication of patients after acute traumatic spinal cord injury (SCI) mostly relies on the neurological assessment of residual function attributed to lesion characteristics. With emerging treatment candidates awaiting to be tested in early clinical trials, there is a need for wholistic high-yield prognostic biomarkers that integrate both neurogenic and nonneurogenic SCI pathophysiology as well as premorbid patient characteristics. Recent findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Samples regarding the MS dataset used in the study are all from peripheral blood; therefore, we only need to collect peripheral blood from MS patients and evaluate the expression of the five discovered immune-associated genes to infer the probability of AVC incidence in MS patients, which is an efficient and practical method for clinical usage. The application of peripheral blood tests in diagnosing different diseases has also been widely accepted ( 34 , 35 ). Moreover, although we confirmed that gene expression level can be used as an independent diagnostic marker, we intend to develop a more comprehensive diagnosis pattern by converting it into a score and taking all these five markers into consideration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Samples regarding the MS dataset used in the study are all from peripheral blood; therefore, we only need to collect peripheral blood from MS patients and evaluate the expression of the five discovered immune-associated genes to infer the probability of AVC incidence in MS patients, which is an efficient and practical method for clinical usage. The application of peripheral blood tests in diagnosing different diseases has also been widely accepted ( 34 , 35 ). Moreover, although we confirmed that gene expression level can be used as an independent diagnostic marker, we intend to develop a more comprehensive diagnosis pattern by converting it into a score and taking all these five markers into consideration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Wang et al 2018) More recently, circulating white blood cell populations have also been identified as potential SCI injury biomarkers, with a 2021 study showing that elevated levels of neutrophils were associated with no AIS grade conversion, while conversely an increase in lymphocytes during the first week post-SCI were associated with an AIS grade improvement. (Jogia et al 2021) A number of individual proteins have been shown to be altered in the bloods post-SCI, including multiple interleukins (IL), tumour necrosis factor alpha (TNF-α) and C-reactive protein (CRP). (Segal et al 1997;Hayes et al 2002;Frost et al 2005) 2 Further, changes in inflammatory marker levels detected in acute SCI patients were found to be mirrored in donor-matched blood and CSF, albeit at lower absolute concentrations systemically.…”
Section: Introductionmentioning
confidence: 99%
“…(Wang et al 2018) More recently, circulating white blood cell populations have also been identified as potential SCI injury biomarkers, with a 2021 study showing that elevated levels of neutrophils were associated with no AIS grade conversion, while conversely an increase in lymphocytes during the first week post-SCI were associated with an AIS grade improvement. (Jogia et al 2021)…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Current prognostication of patients after TSCI mostly relies on the neurological assessment of residual function attributed to lesion characteristics [5] . However, it is often impractical to perform these tests soon after patient admission, which is too time-consuming and unreliable in emergency situations, especially if the patient is unresponsive or compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is urgent to select biomarkers that can be easily extractable from clinical data and routinely used across different healthcare institutions, which can indicate the neurologic outcome and prognosis of TSCI, and routine blood samples seem to meet this requirement. Due to blood samples are easily collected when patient admission and often also measured frequently during the rst week after injury, at least for critically ill patients [5] . Any changes of them may be practical and convenient for predicting SCI.…”
Section: Introductionmentioning
confidence: 99%